Interação central entre óxido nítrico, lactato e as células da glia na modulação comportamental de ingestão de água e sódio em ratos - Costa, Francineide Fernandes (2020)
Recent studies from our laboratory have shown that circumventricular organs (CVOs) glial cells are involved in the modulation of the hydroelectrolytic balance. Furthermore, studies has show that “astrocyte-to-neuron lactate shuttle” (ANLS) mechanism is part of the inhibitory pathway to modulate sodium intake through GABAergic interneurons activation. Another neuromodulator of this inhibitory pathway is the nitric oxide (NO), which induces increase in the GABAergic interneurons activity. In addition, NO is an important modulater to astrocytic energy metabolism, inhibiting mitochondrial respiration and stimulating glucose consumption, resulting in astrocytic lactate production. Regarding that, our hypothesis is that in the CVOs astrocyte, NO induces astrocytic lactate production wich through ANLS mechanism modulated water and sodium intake. For that, we used Wistar rats, which were submmited to stereotactic surgery for intracerebroventricular (icv) guide cannula implantation in the lateral ventricle (VL) region. We performed icv microinjection of saline 0,9%; L-NAME (40 μg/0.5 μl- nitric oxide synthase inhibitor); L-lactate (2 μg/0.5 μl); α-CHCA (3 μg/0.5 μl MCT4 inhibitor, an astrocytic lactate transporter) or fluorocitrate (FCt, 8 μg/0.5 μl-glial inhibitor). In another protocol we performed the microinjection of sterile saline 0.9% and α-CHCA (3 μg/0.5) in rats after water deprivation (48h). After microinjections, water and sodium intake were measured at 5, 15, 30, 60 and 120 minutes. We also performed an ex vivo protocol, incubating rat subfornical organ (SFO) for 1h at 37ºC in normal (145mM Na+), normal (145mM Na+) in the presence of Sodium Nitroprusside (SNP, 3mM), hyperosmotic (170mM Na+) and hyperosmotic medium in the presence of L-NAME (500 μM) to measured lactate concentration. The results showed that L-NAME icv increased water and sodium intake, while glia inhibition with FCt did not change water or sodium intake. However, prior FCt microinjection reduced water and sodium intake induced by L-NAME. In addition, L-Lactate icv did not change the basal intake of water or sodium; but abolished water and sodium intake induced by L-NAME. Inhibition of the ANLS mechanism with α-CHCA did not change either water or sodium basal intake, nor water or sodium intake induced by L-NAME. On the other hand, α-CHCA promoted an potentiation in the water and sodium intake induced by water deprivation. We also observed that the submission of ex vivo SFO of animals to hyperosmotic medium promoted an increase in lactate concentration; in contrast, this result did not change in the presence of L-NAME. In addition, the SNP did not change the lactate concentration in normal osmotic medium. The results suggest that there is an central interaction between NO, glial cells and lactate in behavioral modulation of water and sodium intake in normohydrate animals. In addition, the astrocyte-neuron lactate shuttle (ANLS) central mechanism seems to be involved in the modulation of water and sodium intake under conditions of extracellular hypertonicity.